Glycogen Metabolism in Chlamydia-Infected HeLa-Cells - Fan, Victor S. C. (1970)
A difference in glycogen metabolism between two strains of Chlamydia agents was observed which can serve as a taxonomic marker to distinguish C. psittaci from C. trachomatis.